Pengembangan media pembelajaran interaktif ekonomi berbasis telegram bot - Dwi Saputri, Eva; Yudiono, Udik; Walipah, Walipah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
The aim of the research is to make application in the formstandar teaching media products that are feasible to operate in the field of Economics subject matter of fiscal and monetary policy Â in Class XI in MAN 3 Malang-Donomulyo. This study includes Research of Development (R&D) with ADDIE model. The stages of this model consists of 5 phases, namely 1) Analyze (Analysis); 2) Design (Design); 3) Develop (Development); 4) Implement (implementation),; and 5) Evaluate (evaluation. The increase in innovation in this media was examined in detail by media,material, and laguage experts, and direct in-class test werecarried out involving 25 students. The procedure for obtaining data was in the form of qualitative and quantitative.The data procedure was collected through observational studies, question and answer, and question sheets. The result and discussin studies indicate that innovative teaching media with telegram botas as the basis for Economic studies in Class XI IPS MAN 3 Malang-Donomulyo is recommended, because it is shown that the acquisition of media espert checks is in the ery decent category with a percentage of 92,5%. Validation of media experts 92,5% categorized as very feasible, while media esperts obtained a very feasible percetage of 86% so as very as feasible.